Intratympanic Steroid Therapy For Treatment Of Idiopathic Sudden Sensorineural Hearing Loss As Salvage Therapy. (Journal of Pharmaceutical Negative Results, 2022)
Idiopathic sudden sensorineural hearing loss (ISSHL) is the sudden loss of unilateral hearing of unknown etiology. The standard treatment consists of a high dose oral steroid taper. This article serves to review the current study on the use of Intratympanic steroid injections for ISSHL. Purpose- of the study to know the efficacy of Intratympanic steroid therapy in patients with idiopathic sensorineural hearing loss (ISSHL) who had not responded to intravenous treatment. Materials and Methods-Our study consists of 110 patients with refractory ISSHL.Results- overall 60 patients showed improvement in PTA. Conclusions-IST is an effective and safe therapy in sudden sensorineural hearing loss cases that are refractory to standard treatment.